2010
DOI: 10.1002/esp.1955
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Holocene sea levels using U‐Th ages of phreatic overgrowths on speleothems from coastal caves in Mallorca (Western Mediterranean)

Abstract: Phreatic overgrowths on speleothems (POS) are carbonate formations deposited at the water table of caves in unique\ud karstic coastal settings having morphologies that can be directly related to sea level at the time of formation. The U-Th ages of\ud calcite and aragonite overgrowths collected from the modern water table in coastal caves on Mallorca (Cova de Cala Varques A\ud and Cova des Pas de Vallgornera) were determined using high-precision MC-ICPMS techniques. U-Th ages indicate that phreatic\ud carbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
2
28
0
1
Order By: Relevance
“…Phase 4 ( Figure 5D): The cap of the mushroom is the most unusual subunit of the speleothem. To our knowledge, this type of rock facies has never been described in detail from any other cave (one of the few comparable occurrences is probably that described by Tuccimei et al (2010)). The cap facies occurs in a well-defined horizontal band of the cave rooms (i.e., on the top of the mushroom stipe and on the walls surrounding the water pool).…”
Section: Model For Mushroom Speleothem Formationmentioning
confidence: 75%
“…Phase 4 ( Figure 5D): The cap of the mushroom is the most unusual subunit of the speleothem. To our knowledge, this type of rock facies has never been described in detail from any other cave (one of the few comparable occurrences is probably that described by Tuccimei et al (2010)). The cap facies occurs in a well-defined horizontal band of the cave rooms (i.e., on the top of the mushroom stipe and on the walls surrounding the water pool).…”
Section: Model For Mushroom Speleothem Formationmentioning
confidence: 75%
“…Powders for stable isotope analyses ( Figure 3) were obtained with a dental drill. These institutes are renowned for carbonate U-Th dating, producing hundreds of ages per year; chemical preparation of subsamples and mass-spectrometer analytical details are the same as those presented in the following recent research papers for Melbourne (Bajo et al, 2016;Columbu et al, 2017), Bern (Tuccimei et al, 2010;De Waele et al, 2017) and Mainz (Gibert et al, 2016;Obert et al, 2016). The isotope values are reported in the conventional delta notation with respect to VPDB (Table II).…”
Section: Methodsmentioning
confidence: 99%
“…The coastal caves of Mallorca provide the archetype of these SLIPs (Vesica et al, 2000;Dorale et al, 2010;Tuccimei et al, 2010), but they have also been found in Bermuda and elsewhere (Harmon et al, 1978;Grimes, 2001;Urushibara-Yoshino, 2003;Tuccimei et al, 2007). POS also exist at different depths within the flooded passages of Mallorca's coastal caves, thus providing evidence for prior sea-level highstands and lowstands with unprecedented vertical and temporal resolution (Dorale et al, 2010).…”
Section: Phreatic Overgrowths On Speleothems In Littoral Cave Environmentioning
confidence: 99%